If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 7x = 4x Reorder the terms: 7x + 2y = 4x Solving 7x + 2y = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 7x + -4x + 2y = 4x + -4x Combine like terms: 7x + -4x = 3x 3x + 2y = 4x + -4x Combine like terms: 4x + -4x = 0 3x + 2y = 0 Add '-2y' to each side of the equation. 3x + 2y + -2y = 0 + -2y Combine like terms: 2y + -2y = 0 3x + 0 = 0 + -2y 3x = 0 + -2y Remove the zero: 3x = -2y Divide each side by '3'. x = -0.6666666667y Simplifying x = -0.6666666667y
| 9z+5=7x+6 | | 3(2x-6)+6(x-2)=3(3-5x)+5x-7 | | 4(x-2)-3(x-1)=2(x+6) | | (3x-4)(x^2-6x+6)= | | (x+5)(x+5)=25 | | (11+i)+(3-15i)= | | (x^2+15)(x+30)=3000000 | | 6x(x-1)=7-25x | | (x^2+15)(x+30)=300 | | x^2=5(x+280) | | (-4+3i)-(-1+6i)= | | (2x^3+12)(x^2-15)=117 | | (2x^3+12)(x^2-15)=333 | | -4c(3+5)=32 | | (2x^3+12)(x^2-15)=2103 | | (2x^3+12)(x^2-15)=10 | | 9x^2=6x+3 | | (2x^3+12)(x^2-15)=0 | | (2x+4)-3x=-3(x+7) | | (3x+7y^5-5)(13y-7x^2)=3.14 | | t+(-2)=66 | | 4m=m+9 | | 33+(-7)=29+m | | -33+(-7)=29 | | 14y-4=3y | | 2x^2+(3x-5)=37 | | (3x^4+4x^3-5)-(8x^2-5x+8)= | | x-7y-14=0 | | x+2y=-13 | | 176=H+(219) | | (2x^2)=(3x^2-64) | | y=6x+b |